NLP in diagnostic texts from nephropathology [research data] - Legnar, Maximilian; Daumke, Philipp; Hesser, Jürgen; Porubský, Štefan; Popovic, Zoran V.; Bindzus, Jan Niklas; Siemoneit, Jörn-Helge; Weis, Cleo-Aron Thias (Universität, 2022)
This data set contains all annotated topic word tables from the work "NLP in Diagnostic Texts from Nephropathology", as well as all pre-processed a...
Gesehen am 08.06.2022
Keywords: Forschungsdaten; Datenbank